Does Greater Regulatory Burden Lead to More Corruption? Evidence Using Firm-Level Survey Data for Developing Countries. (13th April 2020) - Amin, Mohammad; Soh, Yew Chong
Abstract: It is sometimes thought that regulation often creates opportunities for public officials to extract bribes. If this is true, deregulation offers a simple way of combating corruption. However, empirical evidence on the corruption and regulation nexus is limited. Further, the corruption indices used are based on experts' opinions, which may suffer from perception bias. The present paper attempts to address these shortcomings using firm-level survey data for 131 mostly developing countries on the actual experience of the firms with bribery and regulatory burden. The study examines the level of overall corruption and petty corruption. Exploiting variation in regulatory burden, both within-country and industry-level, a large positive effect of regulatory burden on corruption is found. For the baseline results, the bribery rate is higher by about 0.03 percentage points for each percentage point increase in the regulatory burden. The finding is robust to several controls and endogeneity checks.